Synthesis, characterization and optical properties of ATiO3–Pr thin films prepared by a photochemical method (where A = Ba and Ca). (October 2015) - Cabello, G.; Lillo, L.; Caro, C.; Seguel, M.; Buono-Core, G.E.; Huentupil, Y.; Chornik, B.; Carrasco, C.; Rodríguez, C.A.
Highlights: A method of photochemical deposition has been used to the preparation of (Ba, Ca)TiO3 thin films doped Pr(III). The (Ba, Ca)TiO3 /Pr(III) films under 375 nm excitation shows emissions attributable to 1 D2 → 3 H4 transition of Pr ion. These PL signals decreased above 10 mol% of Pr(III). Analysis suggests the presence of intermediate energy levels in the band gap influences in the PL processes. Abstract: This article reports the characterization and optical properties of (Ba, Ca)TiO3 thin films doped with Pr at different proportions (0–15 mol%). The films were deposited on Si (1 0 0) and quartz substrates using a photochemical method and post-annealed at 900 °C. The evaluation of photo-reactivity of the precursor complexes was monitored by UV–vis and FT-IR spectroscopy. The obtained films were characterized by X-ray diffraction and X-ray photoelectron spectroscopy. The results indicate that Ba, Ca, Ti, O and Pr are present in the form of perovskite. Under UV light excitation (375 nm) the (Ba, Ca)TiO3 –Pr films show the characteristic emissions ascribed to 1 D2 → 3 H4 transition of Pr 3+ ion. The optical measurements show the presence of intermediate energy levels in the band gap which influence the emission processes.